Validation and comparison of aerodynamic modelling approaches for wind turbines. Issue 2 (September 2016) - Blondel, F.; Boisard, R.; Milekovic, M.; Ferrer, G.; Lienard, C.; Teixeira, D.
Abstract: The development of large capacity Floating Offshore Wind Turbines (FOWT) is an interdisciplinary challenge for the design solvers, requiring accurate modelling of both hydrodynamics, elasticity, servodynamics and aerodynamics all together. Floating platforms will induce low-frequency unsteadiness, and for large capacity turbines, the blade induced vibrations will lead to high-frequency unsteadiness. While yawed inflow conditions are still a challenge for commonly used aerodynamic methods such as the Blade Element Momentum method (BEM), the new sources of unsteadiness involved by large turbine scales and floater motions have to be tackled accurately, keeping the computational cost small enough to be compatible with design and certification purposes. In the light of this, this paper will focus on the comparison of three aerodynamic solvers based on BEM and vortex methods, on standard, yawed and unsteady inflow conditions. We will focus here on up-to-date wind tunnel experiments, such as the Unsteady Aerodynamics Experiment (UAE) database and the MexNext international project.